Review Article:The de thematibus (“on the themes”) of Constantine VII Porphyrogenitus. Translated with introductory chapters and notes by John HALDON [Τranslated Texts for Byzantinists, v. 11], Liverpool University Press 2021 - LOUNGHIS, Telemachos (Byzantina Symmeikta, 2022)
Review Article: The de thematibus (“on the themes”) of Constantine VII Porphyrogenitus. Translated with introductory chapters and notes by John Haldon [Τranslated Texts for Byzantinists, v. 11], Liverpool University Press 2021